2006
DOI: 10.1037/0012-1649.42.4.599
|View full text |Cite
|
Sign up to set email alerts
|

What makes a girl (or a boy) popular (or unpopular)? African American children's perceptions and developmental differences.

Abstract: Open-ended questions were used to obtain narrative accounts of what makes a girl (or a boy) popular (or unpopular) at school. The participants were 489 African American students in Grades 1, 4, and 7 recruited from high-risk inner-city neighborhoods. Appearance and self-presentation were mentioned the most in Grades 4 and 7. Prosocial characteristics were especially relevant for popularity in Grade 1, as were studentship in Grade 4 and peer affiliations in Grade 7. Deviant behaviors were nominated for populari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 77 publications
(121 reference statements)
12
95
0
Order By: Relevance
“…Considering the relative stability of sociometric versus perceived popularity (Wu, Hart, Draper, & Olsen, 2001 ), research to date shows greater stability for the latter, over both the short term (from fall grade 9 to spring grade 10; Schwartz et al, 2006 ), and the longer term (popular students from grades 5 to 12; Cillessen & Borch, 2006 ). Some researchers (Estell, 2007 ;Farmer, Estell, Bishop, O ' Neal, & Cairns, 2003 ;Rodkin & Berger, 2008 ;Rodkin, Farmer, Pearl, & Van Acker, 2000Ryan & Shim, 2008 ;Xie et al, 2006 ) assessed perceived popularity using teacher evaluations on the Interpersonal Competence Scale (ICS -T; Cairns, Leung, Gest, & Cairns, 1995 ). The Popularity subscale of the ICS -T includes three items, each rated on a 7 -point scale (e.g., from not popular to very popular with boys/girls , and from lots of friends to no friends ), and has demonstrated good internal consistency ( α = .70 to .91) (Estell, 2007 ;Farmer et al, 2003 ;Rodkin & Berger, 2008 ;Rodkin et al, 2006 ;Ryan & Shim, 2008 ;Xie et al, 2006 ).…”
Section: Methodological Issues In Assessing Perceived Popularitymentioning
confidence: 99%
“…Considering the relative stability of sociometric versus perceived popularity (Wu, Hart, Draper, & Olsen, 2001 ), research to date shows greater stability for the latter, over both the short term (from fall grade 9 to spring grade 10; Schwartz et al, 2006 ), and the longer term (popular students from grades 5 to 12; Cillessen & Borch, 2006 ). Some researchers (Estell, 2007 ;Farmer, Estell, Bishop, O ' Neal, & Cairns, 2003 ;Rodkin & Berger, 2008 ;Rodkin, Farmer, Pearl, & Van Acker, 2000Ryan & Shim, 2008 ;Xie et al, 2006 ) assessed perceived popularity using teacher evaluations on the Interpersonal Competence Scale (ICS -T; Cairns, Leung, Gest, & Cairns, 1995 ). The Popularity subscale of the ICS -T includes three items, each rated on a 7 -point scale (e.g., from not popular to very popular with boys/girls , and from lots of friends to no friends ), and has demonstrated good internal consistency ( α = .70 to .91) (Estell, 2007 ;Farmer et al, 2003 ;Rodkin & Berger, 2008 ;Rodkin et al, 2006 ;Ryan & Shim, 2008 ;Xie et al, 2006 ).…”
Section: Methodological Issues In Assessing Perceived Popularitymentioning
confidence: 99%
“…Although students who experience social preference and popularity tend to engage in more socially competent interactions with peers , studies suggest they are distinct constructs that are associated with divergent outcomes over the course of elementary school (Lease et al, 2002). Xie, Li, Boucher, Hutchins, and Cairns (2006) suggest social preference and popularity begin to diverge sometime between the 2 nd and 4 th grade. That is, who children like or with whom they prefer to play become less important to who students nominate as popular by the 4 th grade.…”
Section: Classroom Peer Ecologies and Student Adjustmentmentioning
confidence: 97%
“…Given that students' centrality and status can differ for boys and girls and across grade levels, we assessed the relationship between both types of attunement and students' social centrality, social preference, and popularity after accounting for student gender and grade level (Gifford-Smith & Brownell, 2003;Rose, Glick, & Smith, 2011;Vu & Locke, 2014;Xie et al, 2006). We also included minority status as a covariate; research findings are inconsistent regarding the role of minority status in younger students' peer relationships, with little study of minority group differences among early elementary school children (Bellmore, Nishina, & Graham, 2011;Graham, Taylor, & Ho, 2009).…”
Section: Broad and Precise Attunement To Peer Group Affiliationsmentioning
confidence: 99%
“…Some research findings point to a positive relationship between overt aggression and popularity among peers for minority youth (LaFontana and Cillessen 2002). However, more recent findings show that inner city African American children's perceptions of the link between a peer's aggression and popularity follows normative developmental patterns that resemble those of children from different ethnic backgrounds (Xie et al 2006). Research has also demonstrated that minority youth who are seen as aggressive are likely to be less socially preferred by peers (Waasdorp et al 2013).…”
Section: Discussionmentioning
confidence: 94%